Brand Platform as an Element of a Company Marketing Strategy - Nadezhda A. Goncharova; Tatyana Zh. Solosichenko; Natalia V. Merzlyakova (International Journal of Supply Chain Management, 2019)
Abstract- The gist of this article boils down to the comprehensive understanding of the company brand by consumers of linguistic services in a turbulent competition. Development of a brand platform is a stage in building a marketing strategy, which is the foundation for creating a brand. The effective marketing strategy of the company should include the stage of developing a brand platform and be at the forefront in importance, among other issues. And how the company promotes itself in the market, how it promotes itself in the minds of consumers, partners, suppliers, and the media will determine the successful achievement of its strategic goals. Despite the crisis situation, difficult political situation and high rates of foreign currencies, there is still a need for the population to learn English. In this regard, the formation of a marketing strategy and its brand platform of the linguistic center in this market are important, because without it the market will belong exclusively to competitors. Based on the brand platform, the company management understands what consumers are interested in and plans a policy for further development. As part of the marketing strategy a brand platform was proposed for the company. Based on the selected target segment, positioning was carried out based on three points of differentiation: the result for everyone, the simplicity and uniqueness of the methodology and the learning speed. Final positioning concept is formulated in the paper.